Soybean in succession to the residue of the sorghum/Paiaguás grass straw with Azospirillum brasilense - Hisashi Nakao, Allan; Andreotti, Marcelo; de Asevedo Soares, Deyvison; Modesto, Viviane Cristina; Pontes Pechoto, Eduardo Augusto; Alves Freitas, Leandro (Revista Ceres, 2025)
One of the alternatives to achieve agriculture with sustainability and reduction in production costs, mainly with fertilizers, is the formation of straw from the previous crop and the use of genus Azospirillum bacteria. The objective of this study was to evaluate the agronomic characteristics and yield of soybean, cultivated in areas under straw of sorghum regrowth inoculated or not with diazotrophic bacteria, single or intercropped with Paiaguás grass under Integrated System of Agricultural Production, in Cerrado region. The experiments were carried out in the field, in 2015 and 2016, in Selvíria, state of Mato Grosso do Sul. It was used a complete randomized block design, in a 2 x 2 x 2 factorial arrangement, with four replications, in two agricultural years: with the cultivation of dual-purpose and grain sorghum, single or intercropped with Paiaguás grass, with or without inoculating sorghum seeds with the bacterium Azospirillum brasilense. Soybean production and yield components were evaluated. Inoculation of grain or dual-purpose sorghum seeds with Azospirillum brasilense intercropped with Paiaguás grass, before soybean cultivation, increased the components of production and grain yield of soybean in succession.